Electrochemical oxidation of ascorbic acid using MgB2-MWCNT modified glassy carbon electrode - Banan, Darlene; Tan, Wee Tee; Sulaiman, Yusran; M. F., Yusri; Zidan, Mohammed; Ab. Ghani, Sulaiman (Electrochemical Science Group, 2013)
The electrochemical properties of ascorbic acid (AA) have been studied using cyclic voltammetry technique at the surface of MgB2-MWCNT mixture modified glassy carbon electrode (MgB2-MWCNT/GCE) via mechanical attachment method. An enhancement factor of the ascorbic acid oxidation current by about 2 fold compared to the bare electrode was observed. The current was due to diffusion-adsorption process with diffusion activation energy of 2.7kJmol-1. The MgB2-MWCNT/GCE has a limit of detection of 1.3µM AA with a sensitivity of 76.6 mA M-1AA. Good reproducibility and recovery rate was obtained when determining the presence of AA in real life samples.